Revitalização do ambiente construído com a utilização de resíduos de demolição: um estudo de caso - Heloisa Helena Couto (2011)
The economic growth and demographic expansion of cities has caused an upturn in the construction industry, producing large amounts of debris that add to municipal waste being collected and sent to landfills. With the growth has come illegal construction which often disposes of its waste products in a haphazard manor on the edge of cities, in vacant lots and near highway interchanges. The illegal disposal of this debris in breach of established technical standards brings enormous and irreparable damage to the environment. It pollutes public spaces and shortens the life of landfills, causing degradation of the urban landscape. The object of this paper will be the management and use of plasters developed in research projects conducted earlier, derived from the Solid Waste Construction. The method to be employed in this case study will be qualitative. The purpose of this work is geared towards the creation of a pilot project, self management, with multiple subjects and their roles in the use and application of aggregates, and products developed from RSCCs towards the implementation and use in residential interventions of urban clusters. It will be used a random sampling process as a interdisciplinary approach. It will be chosen one type of residence at Vila Paquetá, the villa suggested by Regional Pampulha, where the composite material and the wall coverings will be developed and used from the construction debris as an alternative material do revitalization and rehabilitation of two contemplated homes, as well, the creation of masonry. Initiatives will create a prime project and self management together with articulations of actors and its functions in the use and application of aggregates and products developed from RSCCs.